Criteria for evaluation the sustainable management and policy of Zawita forest in Duhok Governorate North of Iraq - Zeki M. Akrawee (Mesopotamia Journal of Agriculture)
Ground and space data were used to estimate the values of the criteria which had been developed by international organizations to assess the state of forests which showed, that Zawita are primarily afforest of a tourist, a non-productive forest as it is the duty and the ratio of protective forest area of 15% of the total area of the region, also the wooden stock was calculated of this forest, which is estimated 44 thousand cubic meters to give the study included assessments of most of the indicators developed in this context has been placed in a special table, and through this policy has been developed can be applied to these forests is socialism and politics combined with forest policy and multi-access forests Zawita to achieve production Permanent continuing trends in productivity, tourism, preventive and timber production in the future to be optimal. The complete results of application the criteria of evaluation were putted in special table in the results part.